Peningkatan Kapasitas Petani di Kelurahan Kedungbunder Melalui Sosialisasi Petani Mandiri Pupuk - Eva Nurul Malahayati; Dwi Ahmad Fajar Anwarudin; Indra Kurniawan; Firna Nofitriyana; Deny Iswahyudi; Pramu Adistyan; Auzik Amri Mashula (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The majority of the people of Kedungbunder Village, Sutojayan District, Blitar Regency work as farmers and livestock breeders. Farmers in Kedungbunder Village complain that the price of non- subsidized fertilizer is expensive and subsidized fertilizer from the government is difficult to obtain, thus affecting agricultural productivity. This socialization aims to provide understanding and skills to farmers in making and using liquid organic fertilizer from agricultural waste and natural materials in the environment so that farmers can make fertilizer independently. In this way, farmers in Kedungbunder Village are more independent and creative, do not depend on subsidized fertilizer supplies, and reduce operational costs and agricultural activities remain productive, thereby increasing farmer capacity. The methods used in this community service activity include discourse, discussions, and training. The results of community service showed a positive response of 86.76% of participants to socialization activities.